2019
DOI: 10.1038/s41467-019-09694-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficient allelic-drive in Drosophila

Abstract: Gene-drive systems developed in several organisms result in super-Mendelian inheritance of transgenic insertions. Here, we generalize this "active genetic" approach to preferentially transmit allelic variants (allelic-drive) resulting from only a single or a few nucleotide alterations. We test two configurations for allelic-drive: one, copy-cutting, in which a nonpreferred allele is selectively targeted for Cas9/guide RNA (gRNA) cleavage, and a more general approach, copy-grafting, that permits selective inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(114 citation statements)
references
References 36 publications
(37 reference statements)
9
96
5
Order By: Relevance
“…Here, using a split-drive design, we were able to carefully assess the effects of timing, expression and inheritance of Cas9 on both homing and cleavage efficiencies. As reported previously, we found that maternal Cas9 protein deposition was sufficient to induce shadow drive (Guichard et al, 2019) in addition to high rates of F 1 somatic LOF mutations Lin and Potter, 2016;Oberhofer et al, 2018;Port et al, 2014). However, unexpectedly we found that embryonic expression of Cas9 was also sufficient to induce cleavage and homing.…”
Section: Somatic Expression Of Cas9 Results In High Mutagenesis Ratessupporting
confidence: 85%
See 2 more Smart Citations
“…Here, using a split-drive design, we were able to carefully assess the effects of timing, expression and inheritance of Cas9 on both homing and cleavage efficiencies. As reported previously, we found that maternal Cas9 protein deposition was sufficient to induce shadow drive (Guichard et al, 2019) in addition to high rates of F 1 somatic LOF mutations Lin and Potter, 2016;Oberhofer et al, 2018;Port et al, 2014). However, unexpectedly we found that embryonic expression of Cas9 was also sufficient to induce cleavage and homing.…”
Section: Somatic Expression Of Cas9 Results In High Mutagenesis Ratessupporting
confidence: 85%
“…Consistent with previous studies, we also found that maternal deposition of Cas9 protein into the embryo can result in both cleavage and homing in the germ cells (Guichard et al, 2019). In addition to this observation, we also found that paternal Cas9 protein deposition was not sufficient to induce either cleavage or homing, presumably due to the low quantities of Cas9 carried by the sperm into the egg.…”
Section: Resistant Alleles Accumulate Over Subsequent Generationssupporting
confidence: 92%
See 1 more Smart Citation
“…2). Such phenomenon has been observed with gene drive constructs that were not inserted initially at the target site but at another position in the genome (Gantz and Bier 2015;Guichard et al 2019) . The probability of such an event will depend on the length of the flanking homology arms, their percentage of identity,the length of the DNA sequence in between and the position of the donor sequence relative to the cut site (Wang et al 2017) .…”
Section: Probability That the Gene Drive Cassette Inserts Near The Tamentioning
confidence: 72%
“…If the gene drive was designed to eliminate a target population, then it is more likely to eliminate the non-target species. The drive may also have unexpected effects, for example mosaicism due to perdurance of Cas9 expression (Guichard et al 2019) .…”
Section: Discussionmentioning
confidence: 99%